Bangladeshi university EFL teachers’ vision for the future role of artificial intelligence in teaching and teachers’ new identity - Hasan, Md. Mahadhi; Fatema, Kaniz; Mahmud, Rashed (Institute of Advanced Engineering and Science, 2026)
Global education has seen the rapid integration of artificial intelligence (AI). However, its adoption in Bangladeshi universities has been limited, raising questions about the perceived value and future applications of AI among English language teachers. This study examines how English as a foreign language (EFL) teachers at Bangladeshi universities envision a future role for AI in language instruction and discusses how the integration of AI might redefine their professional identity. The data were collected through a survey of 123 EFL teachers from 20 universities, using simple random sampling, and in-depth interviews with five teachers selected through purposive sampling, following a mixed-method approach. Quantitative analysis, supported by descriptive statistics, multicollinearity tests, and multiple regression, revealed that perceived usefulness has a significant impact on teachers’ attitudes toward AI, with a coefficient of 0.643 and a p-value of less than 0.001. In contrast, perceived challenges do not significantly influence attitudes, with a coefficient of 0.032 and a p-value of 0.665. Qualitative findings further illustrate the evolution of professional identity, where teachers acknowledged the potential of AI to change practice through task automation and personalization; however, concerns remain about changes in roles and gaps in skills. Piloting and expert review, together with rigorous statistical procedures, were used to ensure the reliability and validity of the research. The study concludes by stating that the effective integration of AI requires demonstrating its practical benefits and addressing the barriers, thereby providing valuable insights for policy and practice in Bangladeshi universities.